(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The current study investigated the effects of supplying ruminally protected amino acids (AA) (lysine, L; and methionine, M) and dietary protein levels on the performance of late-nursing ewes. Materials and Methods: Thirty-one Awassi ewes nursing single lambs were individually housed and assigned randomly to one of four treatment groups (2 × 2 factorial design). Ewes in treatment groups were (with supplemental RPL and RPM) or were not (without supplemental RPL and RPM) supplemented with lysine (8.5 gm/day) and methionine (4 gm/day) and were fed diets containing either 13.2 (moderate protein) or 11.1% (low protein) protein. Results: No interactions between supplemental AA and dietary protein levels were observed. Supplying ewes with L and M did not affect (p ≥ 0.06) their nutrient intake or their final body weights (BWs). Additionally, milk composition, yield, and efficiency were not affected by supplemental L and M. Decreasing dietary protein levels did not affect (p = 0.13) the final BWs, milk yield, composition, and efficiency but decreased (p < 0.01) nutrient intake of ewes. Conclusion: Under our study conditions, reducing the protein contents of the diets from 13.2% to 11.1% had no negative impact on late-nursing ewes. Regardless of dietary protein level, the beneficial effect of supplying L and M was not evident. J. Adv. Vet. Anim. Res., 11(3): 711-716, September 2024 http://doi.org/10.5455/javar.2024.k821